Hand Colonization with Gram-Negative Organisms of Healthcare Workers Accessing the Cardiac Intensive Care Unit: A Cross-Sectional Study at the Uganda Heart Institute. (9th October 2019) - Ssemogerere, Lameck; Sendagire, Cornelius; Mbabazi, Ceaser; Namungoma, Yvonne; Oketayot, Anna Noland; Namuyonga, Judith; Mijumbi, Cephas; Nkwine, Ritah; Othin, Moses; Oketcho, Michael; Magala, John Paul; Lwabi, Peter; et al.
Abstract : Background . Hands of healthcare workers (HCWs) are vehicles for pathogens responsible for healthcare-associated infections (HAIs). Following the identification of Gram-negative organisms (GNOs) in all cases of HAIs in the cardiac intensive care unit (ICU), we sought to determine the burden of hand colonization with GNOs among healthcare workers who access the cardiac ICU. Methods . We retrospectively reviewed results from surveillance cultures of fingertip imprints of HCWs who access the cardiac ICU at the Uganda Heart Institute. We collected data on staff category, isolates, and susceptibility to antibiotics. We analyzed the data using Microsoft Excel, and the results are summarized in proportions and percentages and presented in charts and tables. Results . Fifty-six healthcare workers participated in the surveillance. 21 were ICU clinicians, 21 non-ICU clinicians, and 14 nonclinicians. GNOs were cultured in 19 (33.9%) HCWs, in which 8/19 (42.1%) were non-ICU clinicians, 6/19 (31.2%) ICU clinicians, and 5/19 (26.3%) nonclinicians. 32 isolates were identified, of which 47%, 28%, and 25% were cultured from non-ICU clinicians, nonclinicians, and ICU clinicians, respectively. Predominant isolates were Acinetobacter (34%), Citrobacter (21.9%), and Pseudomonas (21.9%). Antimicrobial resistance ranged from 4% to 90%. 9/28 (32.1%) isolates, predominantly Acinetobacter species (spp), were carbapenem resistant. 8/28 (28.6%) isolates, predominantly Citrobacter spp, were multidrug resistant. Resistance to ciprofloxacin and cefepime was low at 3.6% and 4.4%, respectively. Conclusion . Gram-negative organisms, predominantly Acinetobacter, Citrobacter, and Pseudomonas spp, were prevalent on the hands of HCWs who access the cardiac ICU irrespective of the staff category. Antimicrobial resistance was high, with multidrug resistance and carbapenem resistance common among Citrobacter spp and Acinetobacter spp, respectively. Resistance to cefepime and ciprofloxacin was low.